2020
DOI: 10.1590/1678-4324-2020190339
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Orthodontic Wires Coated with Silver Nanoparticles

Abstract: Conventional orthodontic treatment with the use of stainless steel may be detrimental to oral health by promoting demineralizing lesions appearance and increasing adhesion and formation of bacterial biofilm, inducing the development of cavities. An alternative that has been researched to reduce the side effects of orthodontic treatment is the coating of materials with antimicrobial nanoparticles. Nanometric-sized particles increase their surface area and contact with the microbial membrane, consequently intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…This may be attributed to the difference in the delivery systems [ 45 ]. Many studies attempt to coat orthodontic archwires with different antimicrobial agents trying to reduce oral microbiomes like photocatalytic TiO 2 [ 46 ], silver material to coat stainless steel and NiTi archwires [ 47 ], N-doped TiO 2 to coat composite, NiTi and SS wires [ 48 ], and silver nanoparticles to coat stainless steel archwires [ 49 ]. The closeness of orthodontic archwires to the enamel surface makes them the most suited and practical vehicle for the delivery of antimicrobial compounds where they are most needed.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the difference in the delivery systems [ 45 ]. Many studies attempt to coat orthodontic archwires with different antimicrobial agents trying to reduce oral microbiomes like photocatalytic TiO 2 [ 46 ], silver material to coat stainless steel and NiTi archwires [ 47 ], N-doped TiO 2 to coat composite, NiTi and SS wires [ 48 ], and silver nanoparticles to coat stainless steel archwires [ 49 ]. The closeness of orthodontic archwires to the enamel surface makes them the most suited and practical vehicle for the delivery of antimicrobial compounds where they are most needed.…”
Section: Discussionmentioning
confidence: 99%
“…Antibacterial properties were demonstrated against oral streptococci using resin composites containing silverimplanted fillers. Gonçalves et al (2020) investigated the effects of various silver NP levels in an empirical composite adhesive comprising silica nanofillers. According to this paper, adding silver NPs to orthodontic adhesive dramatically reduced cariogenic streptococci adherence compared to typical adhesives without sacrificing physical characteristics.…”
Section: Nanofillers or Nps (Tio 2 Silver) Being Incorporated Into O...mentioning
confidence: 99%
“…Silver nanoparticles (Ag NPs), have become common materials in the fields of dentistry and orthodontics due to their high antibacterial activity. Studies have shown that without changing the physical and chemical properties of archwires, the silver nanoparticle coated Abzil ® archwires showed a significant reduction in the presence of S. aureus and S. mutans, while Orthometric ® archwires did not ( Goncalves et al, 2020 ). The nano-silver coated bracket shows great antibacterial characteristic against S. mutans , and its contact inhibition feature is effective especially in the reduction of smooth surface caries around the brackets ( Ghasemi et al, 2017 ; Metin-Gürsoy et al, 2017 ).…”
Section: Antibacterial Coating Materialsmentioning
confidence: 99%